Teknik Instruksional Pertanyaan di Tahap Presenting Theoretical Background to Class and Discussion about the Issue Pembelajaran Berbasis Proyek untuk Meningkatkan Skor Hierarki Peta Konsep Peserta Didik - Dewi, Akta Wahyu Kumala; Muzzazinah, Muzzazinah; Widoretno, Sri (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
The study aimed to calculate hierarchy score on concept map (CM) by applying questions as instructional technique in presenting theoretical background to class and discussion about the issue of project based learning. The subjects were 35 high school students. Research is a classroom action research with research procedure includes: planning for preparing RPP and its completeness, execution on action activity, observation to calculate hierarchy CM score and reflection for next action. Triangulation validation tests include: verification of conformity of CM hierarchy scores and documentation by expert hierarchy of CM and interviews to represent mastery of concept classification. Reduction to select data completeness, data presentation and conclusion based on complete hierarchy data. Data analysis with qualitative descriptive. The results showed hierarchy scores based on expert hierarchy of CM on prasiklus scored below 25.71% on average of total students, while cycle I and cycle II fell to 11.43% and 0%. Above average hierarchy score on prasiklus was obtained at 11.43%, while cycle I went down to 0% and cycle II was obtained 48.57% improvement, thus question as instructional technique in presenting theoretical background to class and discussion about the issue project based learning increasing the hierarchy CM scores both individual and classical